Evaluation of Toxicity and Antiangiogenic Activity of Murraya koenigii Leaf Extracts in Zebrafish - Dinesh, Deeksha; Nanjappa, Dechamma Pandyanda; Babu, Nishith; Kalladka, Krithika; Chakraborty, Gunimala; Chakraborty, Anirban (Journal of Health and Allied Sciences NU, 2020)
Introduction This study aimed to evaluate the toxicity and the antiangiogenic activity of Murraya koenigii leaf extracts in zebrafish.Materials and Methods Crude aqueous and ethanol extracts of M. koenigii leaves were obtained following a standard solvent-based extraction method. The toxicity of these extracts on zebrafish embryonic development was determined and the LC50 values were calculated. Finally, the antiangiogenic activity of the M. koenigii leaf extracts was evaluated in a transgenic zebrafish (Tg [fli1: GFP]) that express GFP under the control of fli1, a transcription factor involved in vasculogenesis.Results The LC50 value of the aqueous extract of M. koenigii leaves was much larger (2,450 ppm) compared with that of ethanol extract (9.85 ppm), suggesting a lower toxicity of the aqueous extract. The antiangiogenic activity was evident only in aqueous extract, with significant effects in formation of intersegmental vessels and subintestinal veins in treated Tg (fli1: GFP) zebrafish embryos.Conclusion This study demonstrated the biological activity of M. koenigii leaf extracts as angiogenesis suppressor, suggesting its therapeutic potential as an angiogenesis inhibitor. Identification of active components from natural sources with potent antiangiogenic activity could lead to the development of anticancer agents.
Keywords: Murraya koenigii leaves; embryo; toxicity; zebrafish; antiangiogenic activity; Tg (fli1: GFP)